Kemandirian Anak Usia 5-6 Tahun Ditinjau dari Pola Asuh Keluarga - Firdausah, Sintana Nirwani; Khasanah, Ismatul; Chandra, Anita (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
A child's independence is largely determined by the parenting style used by parents towards their child. The samples in this study were children aged 5-6 years. The data analysis method uses the Spearman rank test. The research results show that the majority of children have very good independence and democratic parenting. The results of the hypothesis test show that there is a significant difference between parenting patterns and children's independence. This means that the type of parenting style influences the child's independence.